Plans, public policies and strategies of oral health in Latin America and Caribbean (1991-2018) - John M León Quenguan; Anderson E Tibaná Guisao; Jonhatan D Cardona Hincapié; Laura M Correa Jaramillo; Andrés Alonso Agudelo Suárez (Editorial Ciencias Médicas, 2021)
Introduction: The identification of public policies and strategies in oral health, as well as its purposes, actions and limitations is an important step in intersectoral action in health to achieve equity. Objective: To describe the main characteristics of the documents related to oral health plans, policies and strategies in Latin America en the Caribbean. Methods: An exploratory study was conducted by means of documentary analysis of secondary sources of information available on the websites of the ministries of health of 23 countries, and systematic search in the Google, without spatio-temporal restriction. Quantitative and qualitative content analysis was performed. Results: 85 documents were analyzed. The countries with the highest number of documents related to the research topic were Colombia (n = 14), Mexico (n = 8) and Panama (n = 7). A good part is focused on specific populations, such as pregnant women, socially vulnerable communities, school children, teachers, among others. Their purpose is to reduce risk factors for the main oral diseases, making important advances in approaches related to social determinants. However, the gender approach is more timid by focusing attention on the oral health special needs of women in pregnancy, childbirth and postpartum. The main objectives of most of the documents analyzed consisted of an integral attention on the state of oral health, applying education, promotion and clinical activities to the population, according to their needs. Conclusions: An important representation of countries with documents related to national or local programs and plans were found and they have indicators that reflect their compliance. Also practical action guides were described. Although many professionals, especially in dentistry, intervene in the design and construction of documents, the participation of other areas of knowledge is lacking, what will help to achieve a broader vision towards the social determination of health.